On deploying vehicular communication at the developing seaport and related innovation success impediments - Bauk, Sanja; Leon Calvo, Jose Angel; Schmeink, Anke; Azam, Sadia; Mathar, Rudolf (Transport, 2019)
The paper concerns the employment of a vehicular communication concept for traffic management and safety purposes in a developing seaport environment. A general scenario considering centralized and ad-hoc networks has been analysed, since the requirements for the safety of seaports are similar in terms of reliability and latency. The main enhancement of the proposed model is a communication-based cooperative scheme for improving the safety of workers and optimizing the management of on-port vehicles. The simulation analyses have been realized over the container terminal of the developing Port of Bar (South-East Adriatic Sea, Montenegro). Considering the fact that it operates in transitional conditions, related innovation success impediments have been taken into consideration, as well.